Hak Ex Officio Haki Pengadilan Agama Wamena dalam Perkara Nafkah Pasca Perceraian - Labib, Ali Zia Husnul (Fakultas Syariah, 2017)
Divorce has legal consequences, both for husband and wife and children. One of them is living for children. Child income is often not the focus of the discussion in divorce. Large potential children become victims of divorce from their parents. This article aims to describe the ex officio rights of Wamena Religious Court judges in giving ultra petita decisions to the wages of their wives and children after divorce along with the legal basis used. This research is included in empirical legal research using a case study approach. Primary data sources processed from the results of in-depth interviews with judges at the Wamena Religious Court. Decision number 21 / Pdt.G / 2015 / PA.W based on the principle of legal certainty, justice, and expediency. This punishment is expected to provide a guarantee in fulfilling a child's living after divorce. The panel of judges uses ex officio rights based on the Supreme Court Jurisprudence of the Republic of Indonesia.Perceraian membawa dampak hukum, baik terhadap suami-istri maupun anak-anak. Salah satunya adalah nafkah bagi anak. nafkah anak sering kali tidak menjadi fokus pembahasan dalam perceraian. Anak berpotensi besar menjadi korban perceraian orang tuanya. Artikel ini bertujuan mendeskripsikan hak ex officio hakim Pengadilan Agama Wamena dalam memberikan putusan ultra petita terhadap nafkah istri dan anak pasca perceraian beserta dasar hukum yang digunakan. Penelitian ini termasuk dalam penelitian hukum empiris dengan menggunakan pendekatan case study. Sumber data primer diolah dari hasil wawancara mendalam dengan para hakim di Pengadilan Agama Wamena. Putusan nomor 21/Pdt.G/2015/PA.W didasarkan pada asas kepastian hukum, keadilan dan kemanfaatan. Penghukuman ini diharapkan dapat memberikan jaminan dalam pemenuhan nafkah anak pasca perceraian. Majelis hakim menggunakan hak ex officio didasarkan pada Yurisprudensi Mahkamah Agung Republik Indonesia.